2015
DOI: 10.1007/s10856-015-5463-x
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar interbody fusion with porous biphasic calcium phosphate enhanced by recombinant bone morphogenetic protein-2/silk fibroin sustained-released microsphere: an experimental study on sheep model

Abstract: Biphasic calcium phosphate (BCP) has been investigated extensively as a bone substitute nowadays. However, the bone formation capacity of BCP is limited owing to lack of osteoinduction. Silk fibroin (SF) has a structure similar to type I collagen, and could be developed to a microsphere for the sustained-release of rhBMP-2. In our previous report, bioactivity of BCP could be enhanced by rhBMP-2/SF microsphere (containing 0.5 µg rhBMP-2) in vitro. However, the bone regeneration performance of the composite in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The density of the sheep bone used in preclinical orthopedic investigations is typically much greater than that of the target human population for these treatments, and the removal of tissue from the endplates allows for a closer representation of clinical human vertebral bone 32 . It is known that decorticating the bone leads to greater bone formation, therefore removal of tissue from the endplates may have increased the bone formation for all treatments and encouraged callus bone growth around the anterior region of the vertebral body and interbody cage 33‐35 . It is also possible that preservation of the intervertebral endplates may have resulted in decreased bone growth, particularly in sham control animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The density of the sheep bone used in preclinical orthopedic investigations is typically much greater than that of the target human population for these treatments, and the removal of tissue from the endplates allows for a closer representation of clinical human vertebral bone 32 . It is known that decorticating the bone leads to greater bone formation, therefore removal of tissue from the endplates may have increased the bone formation for all treatments and encouraged callus bone growth around the anterior region of the vertebral body and interbody cage 33‐35 . It is also possible that preservation of the intervertebral endplates may have resulted in decreased bone growth, particularly in sham control animals.…”
Section: Discussionmentioning
confidence: 99%
“… 32 It is known that decorticating the bone leads to greater bone formation, therefore removal of tissue from the endplates may have increased the bone formation for all treatments and encouraged callus bone growth around the anterior region of the vertebral body and interbody cage. 33 , 34 , 35 It is also possible that preservation of the intervertebral endplates may have resulted in decreased bone growth, particularly in sham control animals. While the interbody cages were implanted as uniformly as possible, some slight variability in the final placement of the interbody cages is inherent due to the manual implantation process.…”
Section: Discussionmentioning
confidence: 99%
“…MSA is a process by which stable polymers are formed between molecules through noncovalent bonds at the molecular level. , This method involves the use of silk proteins as a template to form mineral structures through the self-assembly of inorganic ions with organic molecules. The self-assembly process is driven by noncovalent interactions between the inorganic and organic components, resulting in the formation of a mineralized composite with controllable size and shape.…”
Section: Silk Proteins As Templates To Guide the Formation Of Mineral...mentioning
confidence: 99%
“…The efficacy of BCP with these rhBMP‐2/SF microspheres were evaluated in a sheep lumbar fusion model. The in vivo results showed that the silk fibroin microspheres including a very low dose of rhBMP‐2 could improve fusion in sheep using BCP constructs (Chen et al, ).…”
Section: Preparation Of Silk Fibroin Carriers For Controlled Releasementioning
confidence: 99%